(untitled) (Aintelia Science Notes, 2023)
In the control of DC-DC converters, pulse width modulation (PWM) is commonly used. In converters operating with PWM control, the switches operate under hard-switching conditions, resulting in increased switching losses, current and voltage stresses on the switching elements, and electromagnetic interference (EMI) noise as the operating frequency increases. Achieving higher power density and faster transient response in DC-DC converters is possible only by increasing the switching frequency. Therefore, reducing these losses and noises while increasing the switching frequency is only possible with soft switching techniques. Particularly in cases of variable loads, such as batteries, and when a smoother output voltage is required, the series-parallel LCC-type circuit topology from resonant converter topologies is employed. In this study, a simple algorithm has been developed to rapidly control the output voltage and switching frequency of the Full-Bridge Isolated LCC Series-Parallel Resonance circuit based on the current drawn by the changing load over time. The circuit has been successfully operated in the range of 100-130 kHz.